Long Noncoding RNAs Regulate the Radioresistance of Breast Cancer - Zhifeng Li; Fujin Wang; Yinxing Zhu; Ting Guo; Mei Lin (Analytical Cellular Pathology)
Breast cancer (BRCA) has severely threatened women’s health worldwide. Radiotherapy is a treatment for BRCA, which applies high doses of ionizing radiation to induce cancer cell death and reduce disease recurrence. Radioresistance is one of the most important elements that affect the therapeutic efficacy of radiotherapy. Long noncoding RNAs (lncRNAs) are suggested to dominate crucial roles in regulating the biological behavior of BRCA. Currently, some studies indicate that overexpression or inhibition of lncRNAs can greatly alter the radioresistance of BRCA. In this review, we summarized the knowledge on the classification and function of lncRNAs and the molecular mechanism of BRCA radioresistance, listed lncRNAs related to the BRCA radioresistance, highlighted their underlying mechanisms, and discussed the potential application of these lncRNAs in regulating BRCA radioresistance.